Development and Characterization of Acellular Caprine Choncal Cartilage Matrix for Tissue Engineering Applications. (December 2021) - Das, Piyali; Rajesh, Kanike; Lalzawmliana, V.; Bavya Devi, K.; Basak, Piyali; Lahiri, Debrupa; Kundu, Biswanath; Roy, Mangal; Nandi, Samit Kumar
Because of poor regenerative capabilities of cartilage, reconstruction of similar rigidity and flexibility is difficult, challenging, and restricted. The aim of the present investigation was to develop cost-effective acellular xenogeneic biomaterial as cartilage substitution. Two novel biometrics have been developed using different chemical processes (Na-deoxycholate + SDS and GndHCl + NaOH) to decellularize caprine (goat) ear cartilage and further extensively characterized before preclinical investigation. Complete cell removal was ascertained by hematoxylin and eosin staining followed by DNA estimation. No adverse effect on extracellular matrix (ECM) was found by quantifying collagen and sulfated glycosaminoglycans (sGAG) content as well as collagen, sGAG and elastin staining. Results showed no drastic changes in ECM structure apart from desired sGAG loss. Scanning electron microscopy images confirmed cellular loss and unaltered orientation. Nano-indentation study on cartilage matrices indicated interesting output showing better results among decellularized groups. Increased elastic modulus and hardness indicated better stiffness and more active energy dissipation mechanism due to decellularization. Fluid uptake and retention property remained unchanged after decellularization as analyzed by swelling behavior study. Additionally, acellular materials were confirmed to be nonreactive and nonhemolytic as assessed by in vitro hemocompatibility study. In vivo study (up to 3 months) on rabbits showed no symptoms of graft rejection/ tissue necrosis, established through postoperative histology and biochemical analyses of tissue explants. With regard to size, shape, biomechanics, source of origin and nonimmunogenic properties, these developed materials can play versatile role in biomedical/ clinical applications and pave a new insight as alternatives in cartilage reconstruction.